2013
DOI: 10.1055/s-0032-1328366
|View full text |Cite
|
Sign up to set email alerts
|

Three Years Follow-up Results of Ranibizumab Treatment for Choroidal Neovascularization Secondary to Pathologic Myopia

Abstract: Treating CNV secondary to PM with ranibizumab during a follow-up of 36 months, we found considerable improvement of visual acuity. Compared to treatment of CNV secondary to exudative age-related macular degeneration, CNVs secondary to PM seem to respond faster to ranibizumab treatment and less injections are neccessary to reach stabilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
2
14
0
1
Order By: Relevance
“…Yet, in a recent retrospective study, Ruiz Moreno et al [11] analyzed the outcomes 4 years after initial treatment with intravitreal bevacizumab or ranibizumab, and found that both drugs had significant and lasting efficacy in 92 patients affected by subfoveal myopic CNV. Further analysis of follow-ups lasting between 36 and 48 months shows that the maintenance of significant visual gains is supported by the studies of Hefner et al [27], Peiretti et al [29], and Franquera et al [28]. In particular, Franquera et al [28], analyzing 40 patients affected by subfoveal or juxtafoveal myopic CNV, found not only significant improvements but also increasing visual gains over the course of follow-up, up to their 36-month examination.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Yet, in a recent retrospective study, Ruiz Moreno et al [11] analyzed the outcomes 4 years after initial treatment with intravitreal bevacizumab or ranibizumab, and found that both drugs had significant and lasting efficacy in 92 patients affected by subfoveal myopic CNV. Further analysis of follow-ups lasting between 36 and 48 months shows that the maintenance of significant visual gains is supported by the studies of Hefner et al [27], Peiretti et al [29], and Franquera et al [28]. In particular, Franquera et al [28], analyzing 40 patients affected by subfoveal or juxtafoveal myopic CNV, found not only significant improvements but also increasing visual gains over the course of follow-up, up to their 36-month examination.…”
Section: Discussionmentioning
confidence: 70%
“…Data in the literature seem to show that their positive effects are maintained even after longer follow-up periods, although some patient series have failed to demonstrate long-term maintenance of the oneyear visual gain [12,[19][20][21][22][23][24][25][26][27][28][29][30][31]. In particular, Voykov et al [23] and Ikuno et al [24] showed a loss of visual benefits at 24-month examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in the treatment of exudative age-related macular degeneration, most authors advocate the use of a PRN regime, where injections are repeated based on predefined reinjection criteria. While an initial ‘upload' with 3 monthly injections at the beginning of treatment is considered a standard treatment in exudative age-related macular degeneration, a swifter treatment response has been observed in pathologic myopia so that most authors recommend a PRN regime immediately after the first injection [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…По данным L. Hefner [51], для купирования активности новообразованных сосудов тре-буется в среднем 3 инъекции (диапазон 1-8) в течение 39,6 мес (диапазон . Перед первой инъекцией острота зрения составляла (LogMAR) 0,69±0,26, через 1 мес она улучшилась до 0,39±0,23 (р=0,002), через 3 мес -до 0,30±0,22 (р=0,002), 6 мес -до 0,30±0,22 (р=0,002).…”
unclassified